’Production efficiency of winter season sunflower (Helianthus annuus) - based cropping systems under Sri Ram Sagar Project command area of Andhra Pradesh - REDDY, M D; KUMAR, K A (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted for 4 years during 1992-93 to 1995-96 to evaluate the production efficiency of 6 winter season sunflower (Helianthus annuus L.) • based cropping systems. The sunflower yield equivalents were higher in sunflower. groundnut (Arachis hypogaea) - greengram (Phaseolus radiatuS L.) cropping system than sunflower - maize (Zea mays L.) - greengrarnj sunflower - sunflower - greengram sunflower- greengram - greengram; sunflower - blackgram (P. mungo L.) - greengram sunflower - sesame (Sesamum indicum L.) - greengram cropping system. The sunflower - groundnut - greengram cropping system was found to be stable (sustainable yield index 70%) with higher production efficiency and net returns compared to other cropping systems. In summer, the sunflower yield equivalents and sustainable yield index were higher in groundnut than that of other crops grown.